Thesis and dissertation writing : a modular approach - Tejero, Erlinda G.; Catchillar, Gerry C. (Mandaluyong City, Philippines : National Book Store, 2006)
This book had been written based on the author's three decades of experience in research in many capacities: as a researcher herself, a research colleague, a thesis and dissertation adviser, an oral defense panelist, and a research consultant.
I. Overview of social science research -- II. The Research problem -- III. The review of related literature -- IV. Research methodology -- V. Statistical treatment of data -- VI. Presentation, analysis, and interpretation data -- VII. Summary, conclusions, and recommendation -- VIII. Form and style in thesis -- IX. Guidelines for writing thesis proposals and dissertation.
Includes index.
Keywords: RESEARCH WRITING